What time the sexton's spade doth rust eaudiobook - Bradley, Alan (Flavia de Luce Mystery, 2024)
NATIONAL BESTSELLER • Amateur sleuth Flavia de Luce, along with her pestilent younger cousin, investigates the murder of a former public hangman and uncovers a secret that brings the greatest shock of her life. “I love the Flavia de Luce novels! Flavia is the best female detective I’ve ever read, full of realism, self-confidence, and emotion (in roughly equal parts), and her tales are hilarious, engaging, and occasionally heartbreaking.”—Diana Gabaldon, #1 New York Times bestselling author of the Outlander series A WASHINGTON POST BEST BOOK OF THE YEAR Flavia de Luce has taken on the mentorship of her odious moon-faced cousin Undine, who has come to live at Buckshaw following the death of her mother. Undine’s main talent, aside from cultivating disgusting habits, seems to be raising Flavia’s hackles, although in her best moments she shows potential for trespassing, trickery, and other assorted mayhem. When Major Greyleigh, a local recluse and former hangman, is found dead after a breakfast of poisonous mushrooms, suspicion falls on the de Luce family’s longtime cook, Mrs. Mullet. After all, wasn’t it she who’d picked the mushrooms, cooked the omelet, and served it to Greyleigh moments before his death? “I have to admit,” says Flavia, an expert in the chemical nature of poisons, “that I’d been praying to God for a jolly good old-fashioned mushroom poisoning. Not that I wanted anyone to die, but why give a girl a gift such as mine without giving her the opportunity to use it?” But Flavia knows the beloved Mrs. Mullet is innocent. Together with Dogger, estate gardener and partner-in-crime, and the obnoxious Undine, Flavia sets out to find the real killer and clear Mrs. Mullet’s good name. Little does she know that following the case’s twists and turns will lead her to a most surprising discovery—one with the power to upend her entire life.